2021
DOI: 10.1101/gad.348320.121
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the m6A RNA modification pathway blocks SARS-CoV-2 and HCoV-OC43 replication

Abstract: N 6 -methyladenosine (m 6 A) is an abundant internal RNA modification, influencing transcript fate and function in uninfected and virus-infected cells. Installation of m 6 A by the nuclear RNA methyltransferase METTL3 occurs cotranscriptionally; however, the genomes of some cytoplasmic RNA viruses are also m 6 A-modified. How the cellular m 6 A modification machinery impacts coronavirus replication, which occurs exclusively in the cytoplasm, is unknown. Here we show that replication of SARS-CoV-2, the agent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 68 publications
8
108
2
Order By: Relevance
“…Depending on the nature of the virus replication, depletion of the m6A machinery may have differential pro-( Courtney et al, 2017 ; Kennedy et al, 2017 ; Lichinchi et al, 2016a ; Tirumuru et al, 2016 ) or anti-viral ( Gokhale et al, 2016 ; Lichinchi et al, 2016b ) impact on viral life cycle ( Hesser et al, 2018 ). Methyltransferase inhibitor DZNep together with siRNA knockdown of MTTL3 (m6A writer), hNRNPA1 (m6A reader) and MAT2A (enzyme that participates in the synthesis of SAM-the universal methyl donor) in Vero cells resulted in a reduced virus yield indicating that the m6A epitranscriptomic machinery facilitates SARS-CoV-2 replication and could serve as a novel target for antiviral drug development which is in agreement with other two recent studies which have demonstrated virus supportive function of METTL3 ( Burgess et al, 2021 ; Li et al, 2021 ). However, in another study, Liu et al (2021) , revealed a negative impact of m6A methylome on SARS-CoV-2 gene expression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Depending on the nature of the virus replication, depletion of the m6A machinery may have differential pro-( Courtney et al, 2017 ; Kennedy et al, 2017 ; Lichinchi et al, 2016a ; Tirumuru et al, 2016 ) or anti-viral ( Gokhale et al, 2016 ; Lichinchi et al, 2016b ) impact on viral life cycle ( Hesser et al, 2018 ). Methyltransferase inhibitor DZNep together with siRNA knockdown of MTTL3 (m6A writer), hNRNPA1 (m6A reader) and MAT2A (enzyme that participates in the synthesis of SAM-the universal methyl donor) in Vero cells resulted in a reduced virus yield indicating that the m6A epitranscriptomic machinery facilitates SARS-CoV-2 replication and could serve as a novel target for antiviral drug development which is in agreement with other two recent studies which have demonstrated virus supportive function of METTL3 ( Burgess et al, 2021 ; Li et al, 2021 ). However, in another study, Liu et al (2021) , revealed a negative impact of m6A methylome on SARS-CoV-2 gene expression.…”
Section: Discussionsupporting
confidence: 89%
“…Depending on the nature of the virus involved, m6A modifications may either support ( Kennedy et al, 2017 ; Lichinchi et al, 2016a ; Tirumuru et al, 2016 ) or inhibit ( Gokhale et al, 2016 ; Lichinchi et al, 2016b ) viral gene expression. Recent studies have mapped eight m6A sites in SARS-CoV-2 genome ( Burgess et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ) and have suggested that m6A pathway positively regulates virus replication. In this study, we extend the role of methylation by elucidating its novel functions in SARS-CoV-2 life cycle (translation-to-replication switch) and propose that inhibition of methylation by chemical inhibitor (DZNep) may provide therapeutic effect against SARS-CoV-2 without inducing an antiviral drug-resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A is one of the host RNA modifications commonly used for epitranscriptomic control of cellular mRNAs. Recent studies have identified m 6 A in SARS-CoV-2 RNA, implying that the virus may utilize this machinery for its own benefit [ 87 , 88 , 89 ]. Several studies in the literature have reported the m 6 A inhibitory effect on SARS-CoV-2 replication.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the modification of viral RNA will strongly impact specific recognition by the NTD as it leads to RNA restructuring 61 . Indeed, Burgess et al found excessive m 6 A methylation of the SCoV-2 genome relevant for viral replication 62 . Interestingly, the 5'-UTR is majorly excluded indicating a role of this region for specific RNPs with unmodified sequences.…”
Section: Discussionmentioning
confidence: 99%